Blood eosinophils as a marker of response to inhaled corticosteroids in COPD. Issue 5 (25th February 2016) - Barnes, Neil C.; Sharma, Raj; Lettis, Sally; Calverley, Peter M.A.
Identification of a biomarker that predicts response to inhaled corticosteroids (ICS) would help evaluate the risk/benefit profile of ICS in chronic obstructive pulmonary disease (COPD) and guide treatment. The ISOLDE study randomised 751 patients (mean post-bronchodilator forced expiratory volume in 1 s (FEV1 ) 1.4 L: 50% predicted normal) to fluticasone propionate 500 μg twice daily or placebo for 3 years, finding no difference in FEV1 rate of decline between treatments (p=0.16) and a significant reduction in median exacerbation rate with fluticasone propionate versus placebo (p=0.026). We re-analysed ISOLDE results by baseline blood eosinophil count to investigate whether eosinophil level predicts ICS benefit. Patients with eosinophils <2% (n=456) had a similar rate of post-bronchodilator FEV1 decline with fluticasone propionate as placebo (–2.9 mL·year −1 ; p=0.688). With eosinophils ≥2% (n=214), the rate of decline decreased by 33.9 mL·year −1 with fluticasone propionate versus placebo (p=0.003). Exacerbation rate reduction on ICS for fluticasone propionate versus placebo was higher in the eosinophil <2% group compared with the ≥2% group; time-to-first moderate/severe exacerbation was not different between treatments in either group. A baseline blood eosinophil count of ≥2% identifies a group of COPD patients with slower rates of decline in FEV1 when treated with ICS: prospective testing of this hypothesis is now warranted. Blood eosinophil level identifies COPD patients showing a slower rate of lung function decline when treated with ICS http://ow.ly/X6HyJ